2019
DOI: 10.1002/ar.24300
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Pleiotropic Functions of Canine β‐Defensin 103: Nasal Cavity Expression, Antimicrobial Activity, and Melanocortin Receptor Activity

Abstract: Canine β‐defensin 103 (cBD103) and its common variant cBD103ΔG23 are multitasking polypeptides. As a β‐defensin, cBD103 is one of many antimicrobial agents used by the innate immunity to thwart pathogenic colonization. In this study, we showed that cBD103 was expressed throughout the nasal cavity, with primary expression in the nares as well as respiratory and olfactory epithelia. In the rostral nasal concha, cBD103 was expressed in the epithelium, and to a lesser degree in the lamina propria, but was absent i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
4
0
1
Order By: Relevance
“…In canines, cBD103 expression was found via RT-qPCR in skin, tongue, lung, epididymis, testes [ 48 ] and the nasal cavity [ 49 ]. We report here the significantly highest expression of cBD103 , followed by cBD102 , Elafin, and cBD1, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In canines, cBD103 expression was found via RT-qPCR in skin, tongue, lung, epididymis, testes [ 48 ] and the nasal cavity [ 49 ]. We report here the significantly highest expression of cBD103 , followed by cBD102 , Elafin, and cBD1, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that cBD1 plays little or no role in the innate defense mechanism of normal AM. Although previous studies suggest mild antimicrobial activities of cBD1, studies on synthesized cBD103 have revealed promising antimicrobial properties in culture environments [ 49 , 50 ]. This may explain the much higher detection of cBD103 than cBD1 in this research, and that cBD103 is essential in CAM to inhibit bacterial growth in the tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse and human β-defensin 1 are also shown to be micromolar MCR agonists [ 55 ]. We recently showed that cBD103ΔG23, the common variant of cBD103, increases ERK1/2 activation and cAMP accumulation when bound to the human or canine MC4R, suggesting that mutations in defensins may influence more than just the immune system [ 125 ].…”
Section: Nonclassical Ligandsmentioning
confidence: 99%
“…Показано, что этот дефенсин конкурирует с α-меланоцитстимулирующим гормоном за связывание с меланокортиновым рецептором 1 (МкР1), а у мышей, трансгенных по этому гену, изменяется не только цвет шерсти, но и вес. Продемонстрировано, что по крайне мере два β-дефенсина человека (hBD1 и hBD3) являются лигандами для МкР1 человека, а изоформа β-дефенсина собаки CBD103 связывается не только с МкР1 собаки, но и с МкР4 человека [54,55].…”
Section: кортикостатическое действие антимикробных пептидовunclassified